Microchemical analyses of otoliths in Baltic Sea fish: Possibilities and limitations of otolith elemental analysis to describe individual life history and stock characteristics of fish in the Baltic Sea - Marohn, Lasse (2011)
In this thesis otolith microchemistry analyses were used to gain insights into the individual life history and stock characteristics of three fish species from the Baltic Sea - the European eel Anguilla anguilla, the Atlantic cod Gadus morhua and the thicklip grey mullet Chelon labrosus. The special hydrographic environment of the world’s largest brackish water system provides promising conditions for the use of otolith elemental analysis to investigate individual migration patterns and stock structures of fish. Here, it was used to gain information with relevance for stock management of fish species that differ widely in their biology, ecology and stock structure. It was investigated whether individual continental migratory history affects health and spawner quality of the European eel. Otolith strontium (Sr) composition was used to identify characteristic migration patterns. Results show that the muscle fat contents of silver eels with strictly catadromous life cycles are significantly reduced compared to silver eels that never entered freshwaters. Furthermore, prevalence and infection intensities of the swimbladder nematode Anguillicoloides crassus are highly increased in catadromous silver eels. Both, a reduced accumulation of fat reserves and intense A. crassus infestations are assumed to impair the successful reproduction of A. anguilla. These results highlight the importance of brackish water habitats for the production of high quality spawners and question the benefit of restocking measures into inland waters. In order to investigate the influence of water temperature and feeding behaviour on the element incorporation into A. anguilla otoliths, two experimental studies were conducted. Results showed that otolith element incorporation is influenced by water temperature, but detected differences between treatments were low to allow an in situ reconstruction of temperature history. In the food experiment no effect on otolith microchemistry was detected between feeding groups. Results indicate that neither ...